Efektivitas Cognitive Behavioral Therapy (CBT) Menurunkan Frekuensi Kekambuhan Penggunaan Narkoba Pada Klien Remaja Di BNN - Hildayanti Hildayanti; Micha Felayati Silalahi; Munifah Munifah; Ridwan Syahran (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study was motivated by the high frequency of relapse into drug use among adolescents after rehabilitation, which is influenced by cognitive, emotional, and environmental factors. The study aimed to analyze the effectiveness of Cognitive Behavioral Therapy (CBT) in reducing relapse frequency among adolescents under the supervision of the National Narcotics Agency in Palu City. The research employed an experimental method using a single-subject A-B-A design consisting of an initial baseline phase (A1), an intervention phase (B), and a final baseline phase (A2). The participant was an adolescent with a history of relapse following rehabilitation. Data were collected through observation, interviews, and repeated recordings of relapse frequency. The results showed a gradual decrease in relapse frequency across the three phases. During the initial baseline phase (A1), relapse frequency was recorded at 8, 7, and 7 occurrences, with an average of 7.33. During the intervention phase (B), the frequency decreased from 7 and 7 to 6, 5, and 4 occurrences, with an average of 5.80. In the final baseline phase (A2), after the intervention had been withdrawn, relapse frequency further decreased and stabilized at 4, 3, and 3 occurrences, with an average of 3.33. Overall, there was a 54.6% reduction in average relapse frequency from the initial baseline phase to the final baseline phase. In addition, the participant demonstrated improved ability to manage negative thoughts, emotions, and environmental pressures more adaptively. These findings indicate that Cognitive Behavioral Therapy is effective in reducing relapse frequency among adolescents. The study highlights the importance of psychological interventions focused on modifying cognitive patterns and behaviors to support the success of adolescent rehabilitation programs.